Assessing hydrologic changes across the Lower Mekong Basin - Lyon, S.W.; King, K.; Polpanich, O.; Lacombe, Guillaume (Elsevier, 2017)
Study region : In this study, 33 catchments across the Lower Mekong Basin in Southeast Asia are examined to detect historical changes in their hydrological response via a model-based methodology. Study focus : Intensive development over the past half century across Southeast Asia’s Lower Mekong Basin has inevitably affected natural resources. Large areas have been converted from forests for subsistence and commercial agriculture, and urban development. We implement an innovative approach to screen hydrologic data for detecting impacts of such large-scale changes on hydrological response. In a first step, temporal changes in the rainfall-runoff relationship were assessed using the parsimonious, two-parameter GR2M hydrological model. In a second step, a distribution-free statistical test was applied to detect whether significant changes have occurred in the wet season (high flow) and dry season (low flow) conditions. New hydrological insights for the region : Our results indicate that the majority of catchments (64% of those considered) with sufficiently long data records exhibited no discernable trends in hydrological response. Those catchments that did exhibit significant trends in hydrological response were fairly evenly split between increasing trends (between 21% and 24%) and decreasing trends (between 15% and 12%) with time. There was a lack of evidence that these changes where brought about by shifts in precipitation or potential evapotranspiration; however, catchments exhibiting significant increasing trends in hydrological behavior were found to have different land cover compositions (lower percentage of forest coverage and subsequently higher paddy rice coverage) than those exhibiting significant decreasing trends. The approach presented here provides a potentially valuable screening method to highlight regions for further investigation of improved mechanistic understanding. Without this connection, we might be blind to future hydrological shifts that can have significant impact on development.